Usability Evaluation of a VibroTactile Feedback System in Stroke Subjects - Held, Jeremia P.; Klaassen, Bart; van Beijnum, Bert-Jan F.; Luft, Andreas R.; Veltink, Peter H. (Frontiers in Bioengineering and Biotechnology, 2017)
Background: To increase the functional capabilities of stroke subjects during activities of daily living, patients receive rehabilitative training to recover adequate motor control. With the goal to motivate self-training by use of the arm in daily life tasks, a sensor system (Arm Usage Coach, AUC) was developed that provides VibroTactile (VT) feedback if the patient does not move the affected arm above a certain threshold level. The objective of this study is to investigate the usability of this system in stroke subjects. Method: The study was designed as a usability and user acceptance study of feedback modalities. Stroke subjects, with mild to moderate arm impairments were enrolled. The subjects wore two AUC devices one on each wrist. VT feedback was given by the device on the affected arm. A semi-structured interview was performed before and after a measurement session with the AUC. In addition, the System Usability Scale (SUS) questionnaire was given. Results: Ten ischemic chronic stroke patients (39 ±38 months after stroke) were recruited. Four out of ten subjects have worn the VT feedback on their dominant, affected arm. In the pre-measurement interview, eight participants indicated a preference for acoustic or visual over VT feedback. In the post evaluation interview, nine of ten participants preferred VT over visual and acoustic feedback. On average, the AUC gave VT feedback six times during the measurement session. All participants, with the exception of one, used their dominant arm more then the non-dominant. For the SUS, eight participants responded above 80, one between 70 and 80 and one participant responded below 50%. Discussion: More patients accepted and valued VT feedback after the test period, hence VT is a feasible feedback modality. The AUC can be used as a tele-rehabilitation device to train and maintain upper extremity use in daily-life tasks.